Spatiotemporal variation of cyanobacterial harmful algal blooms in China based on literature and media information - Yichen Du; Chen Wang; Mengqiu Wang; Huan Zhao; Kai Yan; Yunchang Mu; Wenzhi Zhang; Fangfang Zhang; Shenglei Wang; Junsheng Li (International Journal of Digital Earth, 2023)
Cyanobacterial harmful algal blooms (CyanoHABs) in inland waters are now among the most pressing environmental issues worldwide, especially in China. Satellite remote sensing has limitations in monitoring CyanoHABs in small water bodies due to spatial and temporal resolution limitations. While literature and news media have the potential to supplement satellite remote sensing in monitoring CyanoHABs, they have currently not received sufficient attention. In this study, we combined information on the distributions of CyanoHABs from literature and media for the first time to comprehensively assess the spatiotemporal variation in CyanoHABs in China. We collected, cleaned, validated, and organized data from literature and media on CyanoHABs in China, resulting in the establishment of a comprehensive database on CyanoHABs in China's inland waters (ChinaCyanoDB) covering 198 water bodies, 525 records for 1950–2021. The majority of water bodies with CyanoHABs (CyanoWaters) are located in the eastern China, mainly concentrated in the middle and lower Yangtze region, with a clear upward trend in their number over the last four decades. The ChinaCyanoDB and analytical results can provide valuable data support for monitoring and managing CyanoHABs in China while the database construction method may also be applied to other countries and regions.